MODEL KOOPERATIF TIPE PAIR CHECK DALAM PEMBELAJARAN MEMBACA UNTUK MENINGKATKAN KUALITAS LITERASI - Nurjanah, Nurjanah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper is based on the results of class action research. The study aims to improve the ability to read scanning through a cooperative learning type pair check model on class VIII MTs. Masularul Ulum Pemulutan, Ogan Ilir. The action hypothesis in this study is